(untitled) (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2019)
Is there a particular form of stage writing and direction for contemporary shadow theatre? What are the processes involved in creation? What is the director’s role in designing and directing in shadow production? These are some of the questions that are dealt by Fabrizio Montecchi, according to his theatrical practice and his directing work and which falls within the merits of the most characteristic features of the shadow theatre.